Integration of in situ imaging and chord length distribution measurements for estimation of particle size and shape. (22nd April 2016) - Agimelen, Okpeafoh S.; Jawor-Baczynska, Anna; McGinty, John; Dziewierz, Jerzy; Tachtatzis, Christos; Cleary, Alison; Haley, Ian; Michie, Craig; Andonovic, Ivan; Sefcik, Jan; Mulholland, Anthony J.
Abstract: Efficient processing of particulate products across various manufacturing steps requires that particles possess desired attributes such as size and shape. Controlling the particle production process to obtain required attributes will be greatly facilitated using robust algorithms providing the size and shape information of the particles from in situ measurements. However, obtaining particle size and shape information in situ during manufacturing has been a big challenge. This is because the problem of estimating particle size and shape (aspect ratio) from signals provided by in-line measuring tools is often ill posed, and therefore it calls for appropriate constraints to be imposed on the problem. One way to constrain uncertainty in estimation of particle size and shape from in-line measurements is to combine data from different measurements such as chord length distribution (CLD) and imaging. This paper presents two different methods for combining imaging and CLD data obtained with in-line tools in order to get reliable estimates of particle size distribution and aspect ratio, where the imaging data is used to constrain the search space for an aspect ratio from the CLD data. Abstract : Highlights: Methods for estimating PSD from CLD and images obtained in situ are developed. The particle shape (aspect ratio) is estimated from images obtained in-line. Method 1 reduces uncertainty in the aspect ratio at which PSD is estimated from CLD. Method 2 decouples aspect ratio from the PSD estimation from CLD.